2017
DOI: 10.1016/j.athoracsur.2016.05.049
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes Using a Conservative Versus Liberal Red Blood Cell Transfusion Strategy in Infants Requiring Cardiac Operation

Abstract: Infants undergoing cardiac operation can be managed with a conservative RBC transfusion strategy. Clinical indications should help guide the decision for RBC transfusion even in this uniquely vulnerable population. Larger multicenter trials are needed to confirm these results, and focus on the highest risk patients would be of great interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
81
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(81 citation statements)
references
References 38 publications
0
81
0
Order By: Relevance
“…, Cholette et al . ). Dose of pRBCs administered and the higher pre‐transfusion packed cell volume (PCV) were associated with increased risk for non‐survival in a retrospective study of dogs (Holowaychuk et al .…”
Section: Introductionmentioning
confidence: 97%
“…, Cholette et al . ). Dose of pRBCs administered and the higher pre‐transfusion packed cell volume (PCV) were associated with increased risk for non‐survival in a retrospective study of dogs (Holowaychuk et al .…”
Section: Introductionmentioning
confidence: 97%
“…As a result, the increase of O 2 transport is countered by vasoconstriction and reduced blood flow through the microcirculation, and may not increase O 2 availability. Cholette et al reported similar O 2 extraction rates before and after transfusion in neonates. During their first week of life, neonates have a majority of fetal hemoglobin, which is a high‐O 2 ‐affinity hemoglobin (P 50 = 19.7 mm Hg).…”
Section: Blood Conservationmentioning
confidence: 79%
“…Among 23 neonates undergoing the arterial switch operation with a hemoglobin transfusion trigger of 7 g/dL, Redlin et al reported bloodless CPB in six and bloodless surgery in another six . Recently, Cholette et al reported similar lactate concentrations and clinical outcomes in neonates with hemoglobin concentrations as low as 7 g/dL for biventricular repair and 9 g/dL for palliative procedures (including Norwood procedures), when compared with neonates in whom hemoglobin concentrations were kept above 12 g/dL. On a larger scale, a retrospective analysis of 854 patients, including neonates, showed no significant difference in mortality or severe morbidity in patients receiving “prophylactic” transfusions to maintain hematocrit >20% on CPB, compared with those who received asanguinous prime and only “therapeutic” transfusions after CPB …”
Section: Blood Conservationmentioning
confidence: 99%
See 1 more Smart Citation
“…Salvaging and administration of shed blood from the cell saver can significantly reduce the number of blood and blood product transfusions in the immediate post-operative period (32). Adopting a conservative RBC transfusion approach (transfusing a hemoglobin less than 7.0 g/dL for biventricular repairs or less than 9.0 g/dL for palliative procedures plus clinical indication) has been shown to be effective in reducing RBC transfusion while showing no significant differences in lactate, avO 2 diff, or clinical outcomes (33).…”
Section: The Need and Problems Of Rbc Transfusion During Neonatal Carmentioning
confidence: 99%